Management and outcomes of open pelvic fractures: An update. Issue 10 (October 2021) - Mi, Meng; Kanakaris, Nikolaos K; Wu, Xinbao; Giannoudis, Peter V
Highlights: Adequate resuscitation, blood transfusion, treatment of associated injuries, application of damage control orthopaedics (pelvic ring external fixation +/- C clamp) and soft tissue management are essential in their early management of open pelvic fractures for improved outcomes. A colostomy and cystostomy should be performed in the presence of anorectal and urogenital injuries. Selection of pelvic fixation depends on the type of fracture sustained and the state of the soft tissues. The use of negative pressure drainage is recommended if primary closure of the soft tissue wound is not feasible. Abstract: Background: Open pelvic fractures remain challenging in terms of their management. The purpose of this narrative review was to evaluate the latest advances made in the management of these injuries and report on their clinical outcome. Patients and methods: A literature review was undertaken focusing on studies that have been published on the management of open pelvic fractures between January 2005 and November 2019. Information extracted from each article include demographics, mechanism of injury, injury severity score (ISS), classification of pelvic ring fracture, classification of open soft tissue, specific injury zone classification, number of cases with hemodynamic instability, number of cases that received blood transfusions, amount of packed red blood cells transfused during the first 24 h, number of cases with anorectal trauma, urogenital injury, number of fecal diversional colostomies and laparotomies, angiographies and embolization, preperitoneal pelvic packings, length of stay in intensive care unit (ICU) and in hospital, and mortality. Results: Fifteen articles with 646 cases formed the basis of this review. The majority of patients were male adults (74.9%). The mean age was 35.1 years. The main mechanism of injury was road traffic accidents, accounting for 67.1% of the injuries. The mean ISS was 26.8. A mean of 13.5 units of PRBCs were administered the first 24 h. During the whole hospital stay, 79.3% of the patients required blood transfusions. Angiography and pelvic packing were performed in a range of 3%-44% and 13.3%-100% respectively. Unstable types of pelvic injuries were the majority (72%), whilst 32.7% of the cases were associated with anorectal trauma, and 32.6% presented with urogenital injuries. Bladder ruptures were the most reported urogenital injury. Fecal diversional colostomy was performed in 37.4% of the cases. The mean length of ICU stay was 12.5 days and the mean length of hospital stay was 53.0 days. The mean mortality rate was 23.7%. Conclusion: Mortality following open pelvic fracture remains high despite the evolution of trauma management the last 2 decades. Sufficient blood transfusion, bleeding control, treatments of associated injuries, fracture fixation and soft tissue management remain essential for the reduction of mortality and improved outcomes.